Vascular volumes and hematology in male and female runners and cyclists - Green, H. J.; Carter, S.; Grant, S.; Tupling, R.; Coates, G.; Ali, M. (European Journal of Applied Physiology, 1999)
To examine the hypothesis that foot-strike hemolysis alters vascular volumes and selected hematological properties is trained athletes, we have measured total blood volume (TBV), red cell volume (RCV) and plasma volume (PV) in cyclists (n = 21) and runners (n = 17) and compared them to those of untrained controls (n = 20). The significant correlations (P < 0.05) found between V˙O2peak and RCV (r = 0.64 and 0.64) and TBV (r = 0.82 and 0.63) for the males and females, respectively, suggests a role for the vascular system in realizing a high aerobic power.